A Coalition Game of the Baltic Sea Cod Fishery - Lone Grønbæk Kronbak (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2004)
The paper sets up a discrete-time, deterministic, coalition game model among the major agents exploiting the cod stock in Baltic Sea. The characteristic func-tion is constructed and the Shapley value and the nucleolus are used as one-point solution concepts. The paper identifies the problem with these sharing rules and develops a new sharing rule which takes into account the stability of cooperation. The paper contributes to the literature by introducing a connection between cooperative games (sharing rules) and non-cooperative games (stabil-ity).
Keywords: Q22; 330; Fisheries; Cooperation; Coalition Game; Baltic Sea Cod; Shapley value; Characteristic function; nucleolus; Sharing rules; stability of cooperation; Ostsee; Seefische; Fischerei; Koalition; Spieltheorie; Nordosteuropa; Shapley-Wert